Killing the witches ebook The horror of salem, massachusetts. - O'Reilly, Bill (Bill O'Reilly's Killing., 2023)
The Instant New York Times, Wall Street Journal, and Publishers Weekly Bestseller! Killing the Witches revisits one of the most frightening and inexplicable episodes in American history: the events of 1692 and 1693 in Salem Village, Massachusetts. What began as a mysterious affliction of two young girls who suffered violent fits and exhibited strange behavior soon spread to other young women. Rumors of demonic possession and witchcraft consumed Salem. Soon three women were arrested under suspicion of being witches—but as the hysteria spread, more than 200 people were accused. Thirty were found guilty, twenty were executed, and others died in jail or their lives were ruined. Killing the Witches tells the dramatic history of how the Puritan tradition and the power of early American ministers shaped the origins of the United States, influencing the founding fathers, the American Revolution, and even the Constitutional Convention. The repercussions of Salem continue to the present day, notably in the real-life story behind The Exorcist and in contemporary "witch hunts" driven by social media. The result is a compulsively readable book about good, evil, community panic, and how fear can overwhelm fact and reason.